PERILAKU KONSUMTIF MASYARAKAT INDONESIA DALAM PERSPEKTIF HERBERT MARCUSE - Aziz, Asep Rifqi Abdul (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2022)
Indonesia, which has entered a phase of development both politically and economically, is currently facing a fairly serious problem, namely the problem of a new model of colonialism. It is not colonization carried out by humans on behalf of the state but carried out by a system that has no owner. This system is known as the capitalist system. The capitalist system has an impact on the behavior of the Indonesian people, especially those related to production goods. This phenomenon is called consumptive behavior, namely the excessive use of production goods or services. In turn, consumptive behavior is transformed into a consumptive lifestyle. In this study, consumptive behavior as a bias of the capitalist system or social pathology is exposed through the eyes of Herbert Marcuse who seriously analyzes modern industrial society. The purpose of writing this article is to reveal a new model of slavery carried out by the capitalist system which has a real impact on the consumptive behavior of Indonesian society. One of the causes is stuttering in determining genuine needs with artificial needs. So that a society that only has a one-dimensional view was born. While the method used is a qualitative method sourced from library data. The purpose of this method is to find a one dimensional man ontological basis which can then be used to reveal the social reality of Indonesian society. So that it can provide solutions to the problems that are being faced. The solution offered by Herbert Marcuse is a new society built by progress-oriented young intellectuals who have a multidimensional view.